Type material of Collembola (Hexapoda) housed at the Entomological Collection of La Plata Museum, Buenos Aires, Argentina - Salazar Martínez, Ana Ernestina (2017)
Springtails are entognathous hexapodous (0.2–10 mm) that inhabit in both, aquatic and terrestrial environments. Eighty one type species of Collembola housed at La Plata Museum (Entomology Division) in Argentina were examined and listed. The species are included in forty four genera and sixteen families. Most of the Type specimens belong to Argentinian locations and were described by Eduardo Rapoport, Judith Najt and Dora Cutini de Izarra. Information about type specimens, collection data, descriptions references, other records in Argentina and valid names were provided. Their general known biogeographical distribution and their belonging to ecoregions were included to show the importance of the collection as reference material in Argentina.